World watch geography skill book 3 - Moorcroft, Christine (Oxford University Press, 2022)
World Watch Geography Skill Book 1 is an educational resource designed for young learners to develop foundational geography skills. It covers key geographical concepts such as map reading, landforms, climates, and basic world geography. Through engaging activities and exercises, students learn how to interpret maps, understand spatial relationships, and identify important global features. The book aims to foster curiosity about the world, enhance critical thinking, and build essential geography skills in an interactive and accessible way for beginners.